Identification of miR‐145‐5p‐Centered Competing Endogenous RNA Network in Laryngeal Squamous Cell Carcinoma. Issue 21 (20th June 2019) - Gao, Wei; Zhang, Yuliang; Niu, Min; Bo, Yunfeng; Li, Huizheng; Xue, Xuting; Lu, Yan; Zheng, Xiwang; Tang, Yemei; Cui, Jiajia; He, Long; Thorne, Rick F.; et al.
Abstract: This study intends to investigate the transcriptional regulatory role of miR‐145‐5p in laryngeal squamous cell carcinoma (LSCC). LSCC cell line TU‐177 is transfected with miR‐145‐5p mimics, generating miR‐145‐5p‐overexpression LSCC cells. Whole transcriptome microarrays are used to investigate the differentially expressed lncRNAs, circRNAs, mRNAs, and miRNAs. The target genes of miRNAs are predicted and performed functional annotation. Additionally, the circRNAs, lncRNAs, and mRNAs that interact with miRNAs are predicted, and then the competing endogenous RNAs (ceRNAs) are predicted. Microarray analysis identifies 26 miRNAs, 248 mRNAs, 1118 lncRNAs, and 382 circRNAs differentially expressed in miR‐145‐5p overexpressed LSCC cells. Overall, 675 target genes are identified for the differentially expressed miRNAs, which involved in cell adhesion associated gene ontology (GO) terms, and MAPK and FoxO signaling pathways. The up‐regulated mRNAs involved in the pathway of ABC transporters, while the down‐regulated mRNAs involved in pathway of olfactory transduction. Moreover, 149 ceRNAs are predicted, which are associated with apoptosis, Wnt pathway, and metabolic pathway. Furthermore, qPCR results confirm that miR‐145‐5p affects expression of lncRNAs, miRNAs, mRNAs, and circRNAs in LSCC cells. Collectively, miR‑145‑5p may be inhibits LSCC progression via ceRNA‐mediated pathways, such as WNT2B ‐miR‐145‐5p‐NONHSAT127539.2, CASP10 ‐miR‐145‐5p‐NONHSAT127539.2, CASP10 ‐miR‐145‐5p‐circ_0003519, and TPO ‐miR‐145‐5p‐circ_0003519.